Dearborn Chemical Company water sample testing - Dearborn Chemical Company (1930)
General view of two unidentified men utilizing a Dearborn Chemical Company portable testing cabinet to conduct a water sample field test. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Water purification chemicals industry; Corporations; Glassware; Scientific apparatus and instruments; Water--Analysis; Water--Testing